(untitled) (International Journal of Medical and Surgical Sciences, 2023)
Preeclampsia represents one of the main causes of death in pregnancy, worldwide the WHO indicates that 20% of maternal deaths are caused by hypertensive problems. The problems that represent the highest risk index are hypertension and proteinuria, which are often generated from the 20th week of gestation, up to six weeks after delivery, values that generate a rapid increase of serious complications in preeclampsia including the death of the mother and fetus, However, if the gestational age of the fetus exceeds 36 weeks, the best treatment is the induction of labor, because it reduces the risk of complications, however if it is less than 33 weeks, expectant management including imaging, laboratory and welfare studies for the fetus should be initiated. Thus, it is of significant importance the study that provides the best prenatal control, diagnosis and adequate management of this disease, which are the most effective measures to reduce the mortality rate due to this cause.